Analysis of Leg Muscle Power on Shooting Ability in Students of the Futsal Extracurricular at State Junior High School 11 Banjarbaru - Dimas Anggun Nur Rohmansyah; Ramadhan Arifin; Lazuardy Akbar Fauzan (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to analyze the level of leg muscle power and shooting ability in futsal extracurricular students of state junior high school 11 Banjarbaru. This study uses a quantitative descriptive method with a total sampling technique, so that all 15 students who are members of the futsal extracurricular are used as samples. The instruments used were the standing broad jump test to measure leg muscle power and the goal shooting test to measure shooting ability, with each assessment category having been standardized. The results showed that the majority of students had leg muscle power in the medium category (53%), followed by the poor category (33%), and only 13% were in the good category. Meanwhile, shooting ability was also dominated by the medium category (73.33%), with 20% in the poor category and only 6.67% in the good category. Neither student achieved the excellent category for either variable. These findings indicate that students’ leg muscle power and shooting ability still need to be improved through a more focused and structured training program. This research contributes to providing an empirical picture at the junior high school level and becomes the basis for the development of more effective physical exercises in futsal extracurricular in schools.